Utilization of Coconut Shell as Cr2O3 Catalyst Support for Catalytic Cracking of Jatropha Oil into Biofuel - Isalmi Aziz; Yessinta Kurnianti; Nanda Saridewi; Lisa Adhani; Wahyu Permata (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Coconut shell waste is a waste that has a high carbon content. Carbon in coconut shell waste can be converted into activated carbon having a large surface area. This potential property is suitable to apply the coconut shell as catalyst support. To increase the catalytic activity, metal oxides such as Cr2O3 are impregnated. The purpose of this study is to synthesize Cr2O3/carbon catalyst and test its catalytic activity on catalytic cracking of Jatropha oil. The first stage was the synthesis of activated carbon and the determination of its proximate and ultimate. The second step was impregnation to produce Cr2O3/carbon catalyst. Furthermore, X-Ray Diffraction to determine crystallinity, Surface Area Analyzer to identify its surface area and Fourier Transform Infrared to analyze functional groups. Then the catalytic activity was tested on the catalytic cracking of Jatropha oil. In addition, the chemical compound composition and biofuel selectivity of the catalytic cracking product was determined using Gas Chromatography-Mass Spectrometer. Proximate analysis results showed that activated carbon contains 9%, 1%, 23%, and 67% of water, ash, evaporated substances, and bound carbon, respectively. The results of the ultimate analysis resulted in carbon (C), hydrogen (H), and nitrogen (N) contents of 65.422%, 3.384%, and 0.465%, correspondingly. The catalyst crystallinity test showed the presence of Cr2O3 peaks at 2θ: 24.43°; 33.47° and 36.25° according to JCPDS No. 84-1616. In the absorption area of 400-1000 cm-1 and the range of 2000 cm-1 showed the presence of Cr-O stretching due to Cr2O3 adsorbed into the activated carbon structure. The surface area of activated carbon and Cr2O3/carbon catalysts with a concentration of 1.3, and 5% was 8.930 m2/g; 47.205 m2/g; 50.562 m2/g; and 38.931 m2/g, respectively. The catalytic activity test presented that the best performance was showed by Cr2O3/carbon catalyst with a concentration of 5% indicated by conversion of Jatropha oil into biofuel of 67.777% with gasoline selectivity, kerosene, and diesel of 36.97%, 14.87%, and 15.94%, correspondingly.